Analisis Spasial Kasus COVID-19 sampai dengan PPKM Jilid Dua - Arrazi Rahadiyan; Ernawati Pasaribu (Politeknik Statistika STIS, 2021)
The COVID-19 pandemic is the spread of a disease outbreak infectious COVID-19 caused by infection with SARS-CoV-2 in all countries including Indonesia. As of March 31, 2020, Government Regulation Number 21 of 2020 about Large-Scale Social Restrictions to limit the mobility of people and goods. Governments in each region as well establish quarantine policies in several areas on the islands of Java and Bali based on the Instruction of the Minister of Home Affairs Number 1 of 2021 concerning the Enforcement of Limitations on Community Activities (ELCA) phase 1 and phase 2. This study aims to determine the general description, identify spatial diversity, and analyze factors that influence spatial characteristics of cases COVID-19 in Java and Bali until the period ELCA Phase 2 with Geographically Weighted Negative Binomial Regression. The results of the analysis show that there is a spatial diversity of COVID-19 cases in Java and Bali until the ELCA Phase 2. Density of population that significant effect in all districts/cities in Java, meanwhile the ratio of health workers per 1000 population, air quality index, and health spending has a significant effect only in a few districts/cities on the island Java and Bali.